Experimental radial motion to orbital motion transition in cylindrical Langmuir probes in low pressure plasmas. (16th March 2015) - Díaz-Cabrera, J M; Ballesteros, J; Palop, J I Fernández; Tejero-del-Caz, A
Abstract: This article shows a transition in the behavior of the positive ions movement around a cylindrical Langmuir probe which we have experimentally observed in a low pressure plasma. In the case of helium plasma, depending on the plasma conditions, the ion current collected by the probe behaves as predicted by a radial motion theory, by an orbital motion theory, or by none of them when the transition between the two behaviors takes place. In the case of argon and neon plasmas, the ion current is well described by radial motion theories. The knowledge of the positive ions behavior is essential to diagnose the plasma parameters by using the ion saturation zone of the current–voltage characteristic curve. The use of this zone is one of the less intrusive in probe plasma diagnostics methods providing local information about the plasma parameters, since the charge drained from the plasma is very low.